Labour Management 'Trust Relations' as Reflected in Collective Agreement Clauses - Fricke, John (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1991)
The author makes a critical evaluation of labour management communication clauses in the total population of collective agreements filed with Alberto Labour as of May 31, 1987. This exercise has the aim of finding some indication of joint decision making and conflict handling in the wording and overall presentation of these clauses.